The use of new Dual Lipases System in the synthesis of Ferulate Esters: optimization by response Surface Methodology - Nurul Jannah Abd Rahman
A novel and simple dual lipases system was developed in attaining high performance of ferulate esters by transesterification reaction between ethyl ferulate and olive oil. Detection and identification of reaction products were facilitated by Fourier Transform Infrared (FTIR). Enzyme screening revealed 1: 9 w/w of Novozym 435-Lipozyme RM IM to be the most efficient lipases ratio for the reaction synthesis. By varying one-parameter-at-a-time, 60 degree celcius of reaction temperature, 12 hrs of incubation time, 80 mg of lipase dosage and 1: 2 of ethyl ferulate: olive oil ratio were shown to be the optimal and suitable reaction conditions. Response surface methodology (RSM) based on four-factor-five-level central composite design (CCD) was further used to study the interactive effects among the parameters. The best fitting model was quadratic polynomial where incubation time exhibited most significant effect over the other three parameters. A high percent conversion of 94.03 % was achieved under the optimum conditions, which compared well with the maximum predicted value of 94.83 %. Biological study of ferulate esters was measured based on their antimicrobial properties against both Gram-positive and Gram-negative bacteria. Screening by agar diffusion test was employed as preliminary features followed by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. The results proved that the ferulate esters posses moderate antibacterial inhibition against Gram-positive and Gram-negative bacteria. Their physicochemical properties were also well examined through sun protection factor (SPF) value, peroxidase value, saponification value and iodine value.